Long-Term Mortality Among ICU Patients With Stroke Compared With Other Critically Ill Patients. Issue 10 (October 2020) - van Valburg, Mariëlle K.; Termorshuizen, Fabian; Brinkman, Sylvia; Abdo, Wilson F.; van den Bergh, Walter M.; Horn, Janneke; van Mook, Walther N. K. A.; Siegerink, Bob; Slooter, Arjen J. C.; Wermer, Marieke J. H.; Geerts, Bart F.; Arbous, M. Sesmu
Abstract : Objectives: Assessment of all-cause mortality of intracerebral hemorrhage and ischemic stroke patients admitted to the ICU and comparison to the mortality of other critically ill ICU patients classified into six other diagnostic subgroups and the general Dutch population. Design: Observational cohort study. Setting: All ICUs participating in the Dutch National Intensive Care Evaluation database. Patients: All adult patients admitted to these ICUs between 2010 and 2015; patients were followed until February 2017. Interventions: None. Measurements and Main Results: Of all 370, 386 included ICU patients, 7, 046 (1.9%) were stroke patients, 4, 072 with ischemic stroke, and 2, 974 with intracerebral hemorrhage. Short-term mortality in ICU-admitted stroke patients was high with 30 days mortality of 31% in ischemic stroke and 42% in intracerebral hemorrhage. In the longer term, the survival curve gradient among ischemic stroke and intracerebral hemorrhage patients stabilized. The gradual alteration of mortality risk after ICU admission was assessed using left-truncation with increasing minimum survival period. ICU-admitted stroke patients who survive the first 30 days after suffering from a stroke had a favorable subsequent survival compared with other diseases necessitating ICU admission such as patients admitted due to sepsis or severe community-acquired pneumonia. After having survived the first 3 months after ICU admission, multivariable Cox regression analyses showed that case-mix adjusted hazard ratios during the follow-up period of up to 3 years were lower in ischemic stroke compared with sepsis (adjusted hazard ratio, 1.21; 95% CI, 1.06–1.36) and severe community-acquired pneumonia (adjusted hazard ratio, 1.57; 95% CI, 1.39–1.77) and in intracerebral hemorrhage patients compared with these groups (adjusted hazard ratio, 1.14; 95% CI, 0.98–1.33 and adjusted hazard ratio, 1.49; 95% CI, 1.28–1.73). Conclusions: Stroke patients who need intensive care treatment have a high short-term mortality risk, but this alters favorably with increasing duration of survival time after ICU admission in patients with both ischemic stroke and intracerebral hemorrhage, especially compared with other populations of critically ill patients such as sepsis or severe community-acquired pneumonia patients. Abstract : Supplemental Digital Content is available in the text.